Caffeine consumption and exposure in Saudi Arabia: a cross-sectional analysis - Fallata, Ghadir; Alhumaidan, Omar; Alkhunein, Sarah; Baqadir, Nimah; Bin Sheehah, Rahaf; Binsunaid, Faisal; Alragea, Atheer; Alfayez, Mazen; Bawazeer, Nahla (Frontiers in Nutrition, 2025)
IntroductionCaffeine, a central nervous system stimulant, with 80% worldwide consumption. Despite its popularity, limited research has evaluated caffeine exposure in Saudi Arabia (SA). Given that excessive caffeine intake can cause symptoms such as increased heart rate, headaches, and hyperactivity, understanding community-level consumption patterns is critical. This study aimed to assess caffeine consumption and exposure among Saudi consumers by assessing caffeine consumption levels in the adult population of SA.MethodsA cross-sectional, Internet-based questionnaire study was conducted between September 2021 and January 2022. The questionnaire comprised 92 questions divided into three sections: demographic characteristics, a food frequency questionnaire on caffeine-containing products, and practices related to caffeine consumption.ResultsA total of 1,039 participants were included in the study. The average daily caffeine exposure among Saudi adults was 218 mg/day. The highest caffeine exposure was from hot coffee (64.8 mL/day), soft drinks (41.9 mL/day), iced coffee (35.7 mL/day), tea (26.3 mL/day), energy drinks (16.5 mL/day), and chocolate (3.2 mg/day). This level of consumption falls within the recommended safe limit for healthy adults, which is 400 mg/day.DiscussionCaffeine consumption among Saudi individuals largely falls within the recommended safe range. Further research should investigate the long-term health effects of caffeine, emphasizing the need for public health initiatives to encourage recommended consumption.